Factor influencing use of digital technology among secondary school teachers - Abu Hanifah, Siti Syuhada (2022)
In recent years, the use of digital technology has become vital for individuals to survive in a digital society. In education, digital technology use is becoming a critical component of the development of effective pedagogical practise and student learning enhancement. To meet the demand, this study summarises the findings of an investigation on factors affecting teachers’ digital technology use using an adaption of the Unified Theory of Acceptance and Usage of Technology (UTAUT) and European Framework for Educators' Digital Competences (DigCompEdu). The purpose of this study is to predict a model of the factors that influence secondary school teachers' digital technology utilization. This will be accomplished by determining the level of teachers' digital competence, establishing relationships between constructs such as personal innovativeness, ICT facility, technology self-efficacy, subjective norms, attitude toward digital technology, and digital competence and finally, developing a model. A survey was conducted with 363 secondary school teachers from 50 public secondary schools in 11 districts of Pahang. To obtain the sample, proportionate stratified sampling was used. A quantitative study using the correlational technique has been proposed to address it. The participants were asked to complete a questionnaire related to the constructs. The findings indicate that teachers have an average level of digital competence. In terms of the model, it has been established that personal innovativeness, self-efficacy in technology, subjective norms, and digital competence have a significant effect on teachers’ use of digital technology. However, it was discovered that ICT facilities have no measurable impact on use of digital technology. The overall structural model with six paths has explained 37.6 percent of the variance for use of digital technology among secondary school teachers. The final section of the paper examined possible causes for the study's findings and made recommendations for further research. These findings emphasise the importance of increasing teachers' digital competence as well as numerous factors that influence teachers' use of digital technology in order to fulfil the expectations of future qualified professions and thus prepare students for the digital world.